Surface characterization of nitride structures on Cu(001) formed by N ions implantation: an AES, XPS and LEIS study - Cristina, Lucila Josefina (2008)
By means of Auger electron spectroscopy (AES), X-ray photoelectron spectroscopy (XPS), and low energy ion spectrometry (LEIS) techniques we studied the process of low energy N+2 implantation and annealing of a Cu(001) surface, a proposed model system for self-assembled nanostructures. We characterized the N diffusion features as a function of the substrate temperature and we followed the chemical state of N and Cu along the annealing process. We also took advantage of the LEIS surface sensitivity that, together with its elemental detection capability, can give us insight about the surface structure formation process. We found that the N binding energy shifts non-monotonously along the whole process pointing out that the N–Cu bonding environment is changing and it depends on the atomic rearrangement and on the N amount. We also found that N locates on the fourfold hollow site of the Cu(001) surface. Our LEIS results are compatible with a c(2 x 2) ordering, but at the same time we cannot disregard that some N atoms are either located on other fourfold hollow sites or substituting Cu atoms.